2015
DOI: 10.1111/ctr.12523
|View full text |Cite
|
Sign up to set email alerts
|

High B‐cell activating factor is not associated with worse 3‐year graft outcome in blood group‐incompatible kidney transplantation with rituximab induction

Abstract: B cells and their regulation by B-cell activating factor BAFF are of growing interest in kidney transplantation (KTx). There is evidence that high serum (s) BAFF leads to increased allosensitization and impaired long-term graft function. We prospectively investigated sBAFF, peripheral blood lymphocytes (PBL), and donor-specific HLA antibodies (DSA) in patients after ABOi with B-cell depleting rituximab induction treatment and compared them to a group of blood group-compatible (ABOc) living donor kidney recipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…On the one hand, some authors indicate that BAFF reflects the immunological risk profile of patients after kidney transplantation (KT), considering that pretransplant BAFF levels are associated with pretransplant sensitization and are useful in predicting allograft rejection [23][24][25]; BAFF expression correlates with pretransplant panel reactive antibody (PRA), indicating that BAFF may be involved in the development of graft loss [26]; elevated levels of BAFF are associated with antibody-mediated clinical damage in KT [27], and with an increased risk of acute AbMR [28][29][30]. On the other hand, there are authors that affirm that BAFF is not a prognostic marker for allograft dysfunction or survival in KT patients because BAFF serum levels are not related to anti-HLA sensitization [31]; significantly lower levels of BAFF are found in patients experiencing AbMR [32]; or high BAFF is not associated with the graft outcome in KT with rituximab induction [33]. A meta-analysis published recently evaluated the predictive value of serum BAFF for AbMR, indicating that the incidence of AbMR was significantly higher in patients with high levels of BAFF [34].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, some authors indicate that BAFF reflects the immunological risk profile of patients after kidney transplantation (KT), considering that pretransplant BAFF levels are associated with pretransplant sensitization and are useful in predicting allograft rejection [23][24][25]; BAFF expression correlates with pretransplant panel reactive antibody (PRA), indicating that BAFF may be involved in the development of graft loss [26]; elevated levels of BAFF are associated with antibody-mediated clinical damage in KT [27], and with an increased risk of acute AbMR [28][29][30]. On the other hand, there are authors that affirm that BAFF is not a prognostic marker for allograft dysfunction or survival in KT patients because BAFF serum levels are not related to anti-HLA sensitization [31]; significantly lower levels of BAFF are found in patients experiencing AbMR [32]; or high BAFF is not associated with the graft outcome in KT with rituximab induction [33]. A meta-analysis published recently evaluated the predictive value of serum BAFF for AbMR, indicating that the incidence of AbMR was significantly higher in patients with high levels of BAFF [34].…”
Section: Introductionmentioning
confidence: 99%
“…According to our center’s desensitization protocols, pre-sensitized patients with high PRA or positive HLA-DSA are treated with rituximab (375 mg/m 2 , intravenously) a month before transplantation. B-cell depleting agents such as this have been reported to be associated with significant elevation of serum BAFF levels for more than 1 year after transplantation [ 16 , 21 , 22 ]. Comparison of post-transplant serum BAFF levels in patients who underwent Rituximab therapy and those who did not, showed that post-transplant BAFF levels were significantly higher in patients who underwent Rituximab therapy (median 251.48 pg/mL vs. 80.73 pg/mL in patients without Rituximab therapy, P = 0.000) ( S3A Fig ).…”
Section: Discussionmentioning
confidence: 99%